HOW TO FIND VERTICAL ASYMPTOTE OF A FUNCTION

Vertical Asymptote :

This is a vertical line that is not part of a graph of a function but guides it for y-values 'far' up  and/or 'far' down.

The graph may cross it but eventually, for large enough or small enough values of y, that is

y ----> ±

Always, the graph would get closer and closer to the horizontal asymptote without touching it.

In the diagram above, x = k is an horizontal asymptote. Because, the graph is getting closer and closer to x = k without touching it as y ----> ±.

We will be able to find vertical asymptotes of a function, only if it is a rational function.

That is, the function has to be in the form of

f(x) = g(x)/h(x)

Rational Function - Example :

Steps to Find the Equation of a Vertical Asymptote of a Rational Function

Step 1 :

Let f(x) be the given rational function. Make the denominator equal to zero.

Step 2 :

When we make the denominator equal to zero, suppose we get x = a and x = b. 

Step 3 :

The equations of the vertical asymptotes are 

x = a and x = b

In each case, find the equation of vertical asymptote :

Example 1 :

f(x) = 1/(x + 6)

Solution :

Step 1 :

In the given rational function, the denominator is

x + 6

Step 2 :

Equate the denominator to zero and solve for x.

x + 6 = 0

x = - 6

Step 3 :

The equation of the vertical asymptote is

x = - 6

Example 2 :

f(x) = (x2 + 2x - 3)/(x2 - 5x + 6)

Solution :

Step 1 :

In the given rational function, the denominator is

x2 - 5x + 6

Step 2 :

Equate the denominator to zero and solve for x. 

x2 - 5x + 6 = 0

(x - 2)(x - 3) = 0

x - 2 = 0 or x - 3 = 0

x = 2 or x = 3

Step 3 :

The equations of two vertical asymptotes are

x = 2 and x = 3

Example 3 :

f(x) = (2x - 3)/(x2 - 4)

Solution :

Step 1 :

In the given rational function, the denominator is

x2 - 4

Step 2 :

Equate the denominator to zero and solve for x.

x2 - 4 = 0

x2 - 22 = 0

(x + 2)(x - 2) = 0

x = -2 or x = 2

Step 3 :

The equations of two vertical asymptotes are

x = -2 and x = 2

Example 4 :

f(x) = (2x - 3)/(x2 + 4)

Solution :

Step 1 :

In the given rational function, the denominator is

x2 + 4

Step 2 :

Equate the denominator to zero and solve for x.

x2 + 4 = 0

x2 = -4

x = ±√-4

x = ±2i

x = 2i or x = -2i (Imaginary)

Step 3 :

When we equate the denominator to zero, we don't get real values for x.

So, there is no vertical asymptote.

Kindly mail your feedback to v4formath@gmail.com

We always appreciate your feedback.

©All rights reserved. onlinemath4all.com

Recent Articles

  1. Cross Product Rule in Proportion

    Oct 05, 22 11:41 AM

    Cross Product Rule in Proportion - Concept - Solved Problems

    Read More

  2. Power Rule of Logarithms

    Oct 04, 22 11:08 PM

    Power Rule of Logarithms - Concept - Solved Problems

    Read More

  3. Product Rule of Logarithms

    Oct 04, 22 11:07 PM

    Product Rule of Logarithms - Concept - Solved Problems

    Read More